2007
DOI: 10.1002/hipo.20374
|View full text |Cite
|
Sign up to set email alerts
|

Grid cell firing may arise from interference of theta frequency membrane potential oscillations in single neurons

Abstract: Intracellular recording and computational modelling suggest that interactions of subthreshold membrane potential oscillation frequency in different dendritic branches of entorhinal cortex stellate cells could underlie the functional coding of continuous dimensions of space and time. Among other things, these interactions could underlie properties of grid cell field spacing. The relationship between experimental data on membrane potential oscillation frequency (f) and grid cell field spacing (G) indicates a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
311
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(331 citation statements)
references
References 98 publications
16
311
1
Order By: Relevance
“…The observation of spatial firing patterns in the MEC encouraged us to ask whether the disambiguation of places on the maze by temporal context occurred within the hippocampus or instead occurred earlier in the cortical-hippocampal hierarchy, specifically in the MEC. This possibility is consistent with the suggestion that sequences are bound by a shared temporal context signal that may exist in the entorhinal area (Hasselmo and Eichenbaum, 2005;Hasselmo et al, 2007;Hasselmo, 2007; see also Hasselmo, 2008).…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediasupporting
confidence: 89%
See 1 more Smart Citation
“…The observation of spatial firing patterns in the MEC encouraged us to ask whether the disambiguation of places on the maze by temporal context occurred within the hippocampus or instead occurred earlier in the cortical-hippocampal hierarchy, specifically in the MEC. This possibility is consistent with the suggestion that sequences are bound by a shared temporal context signal that may exist in the entorhinal area (Hasselmo and Eichenbaum, 2005;Hasselmo et al, 2007;Hasselmo, 2007; see also Hasselmo, 2008).…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediasupporting
confidence: 89%
“…Our speculative interpretation that MEC neuronal firing patterns contain a signal for temporal context is based on the observation that MEC spatial firing often extended through a substantial distance on the maze, and these firing patterns varied as a function of trial type. The connection between these two properties may be that sustained firing patterns serve as the neural bridge that links sequential events subsequently identified within the hippocampus, and does so differentially for each trial type (Hasselmo and Eichenbaum, 2005;Hasselmo et al, 2007;Hasselmo, 2007; see also Hasselmo, 2008). In this way, MEC activity that spans multiple spatial locations signals what is common about those locations in terms of an animal's ongoing behavior, that is, a leftvs.…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediamentioning
confidence: 99%
“…A recent model for the grid field properties of the entorhinal cortex layer II stellate cells [22,23,38] relies precisely on the ingredients considered in the present study. The model assumes that different dendritic branches emanating from the soma of these cells function as distinct oscillators.…”
Section: Discussionmentioning
confidence: 99%
“…This model provides an alternate implementation of the oscillatory interference model Burgess, 2008) that is compared to the implementation using membrane potential oscillations Hasselmo et al, 2007;Giocomo and Hasselmo, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling showed that membrane potential oscillations in entorhinal neurons might also contribute to grid cell firing Giocomo et al, 2007;Hasselmo et al, 2007;Giocomo and Hasselmo, 2008a). Entorhinal Layer II stellate cells show subthreshold membrane potential oscillations when depolarized near firing threshold (Alonso and Llinas, 1989;Alonso and Klink, 1993;Giocomo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%